Unpacking the impact of adverse childhood experiences on adult mental health() - Merrick, Melissa T. (Child Abuse Negl, 2017)
Exposure to childhood adversity has an impact on adult mental health, increasing the risk for depression and suicide. Associations between Adverse Childhood Experiences (ACEs) and several adult mental and behavioral health outcomes are well documented in the literature, establishing the need for prevention. The current study analyzes the relationship between an expanded ACE score that includes being spanked as a child and adult mental health outcomes by examining each ACE separately to determine the contribution of each ACE. Data were drawn from Wave II of the CDC-Kaiser ACE Study, consisting of 7465 adult members of Kaiser Permanente in southern California. Dichotomous variables corresponding to each of the 11 ACE categories were created, with ACE score ranging from 0 to 11 corresponding to the total number of ACEs experienced. Multiple logistic regression modeling was used to examine the relationship between ACEs and adult mental health outcomes adjusting for sociodemographic covariates. Results indicated a graded dose-response relationship between the expanded ACE score and the likelihood of moderate to heavy drinking, drug use, depressed affect, and suicide attempts in adulthood. In the adjusted models, being spanked as a child was significantly associated with all self-reported mental health outcomes. Over 80% of the sample reported exposure to at least one ACE, signifying the potential to capture experiences not previously considered by traditional ACE indices. The findings highlight the importance of examining both cumulative ACE scores and individual ACEs on adult health outcomes to better understand key risk and protective factors for future prevention efforts.